Extracellular Matrix Proteins Modulate Antimigratory and Apoptotic Effects of Doxorubicin. (16th May 2012) - Said, Georges; Guilbert, Marie; Morjani, Hamid; Garnotel, Roselyne; Jeannesson, Pierre; El Btaouri, Hassan
Abstract : Anticancer drug resistance is a multifactorial process that includes acquired and de novo drug resistances. Acquired resistance develops during treatment, while de novo resistance is the primary way for tumor cells to escape chemotherapy. Tumor microenvironment has been recently shown to be one of the important factors contributing to de novo resistance and called environment-mediated drug resistance (EMDR). Two forms of EMDR have been described: soluble factor-mediated drug resistance (SFM-DR) and cell adhesion-mediated drug resistance (CAM-DR). Anthracyclines, among the most potent chemotherapeutic agents, are widely used in clinics against hematopoietic and solid tumors. Their main mechanism of action relies on the inhibition of topoisomerase I and/or II and the induction of apoptosis. Beyond this well-known antitumor activity, it has been recently demonstrated that anthracyclines may display potent anti-invasive effects when used at subtoxic concentrations. In this paper, we will describe two particular modes of EMDR by which microenvironment may influence tumor-cell response to one of these anthracyclines, doxorubicin. The first one considers the influence of type I collagen on the antimigratory effect of doxorubicin (CAM-DR). The second considers the protection of tumor cells by thrombospondin-I against doxorubicin-induced apoptosis (SFM-DR).